2008
DOI: 10.1186/cc6958
|View full text |Cite|
|
Sign up to set email alerts
|

Gastrointestinal Failure score in critically ill patients: a prospective observational study

Abstract: Introduction There are no universally accepted diagnostic criteria for gastrointestinal failure in critically ill patients. In the present study we tested whether the occurrence of food intolerance (FI) and intra-abdominal hypertension (IAH), combined in a 5-grade scoring system for assessment of gastrointestinal function (the Gastrointestinal Failure [GIF] score), predicts mortality. The prognostic value of the GIF score alone and in combination with the Sequential Organ Failure Assessment (SOFA) score is eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
150
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(173 citation statements)
references
References 37 publications
3
150
3
8
Order By: Relevance
“…Indeed, the results suggest that patients with higher APACHE II scores are more vulnerable to IAP induced FI [114]. In many other studies, higher severity of illness scores have been reported in patients with IAH, as well as in patients with GI dysfunction and FI [4,19,20].…”
Section: Studies Connecting Iap and Clinical Symptoms Of Gi Dysfunctionmentioning
confidence: 72%
See 3 more Smart Citations
“…Indeed, the results suggest that patients with higher APACHE II scores are more vulnerable to IAP induced FI [114]. In many other studies, higher severity of illness scores have been reported in patients with IAH, as well as in patients with GI dysfunction and FI [4,19,20].…”
Section: Studies Connecting Iap and Clinical Symptoms Of Gi Dysfunctionmentioning
confidence: 72%
“…A higher prevalence of feeding intolerance (FI) in patients with IAH has been demonstrated in several studies [4,114]. Bejarano et al [114] showed that baseline IAP together with an APACHE II score may predict FI.…”
Section: Studies Connecting Iap and Clinical Symptoms Of Gi Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also relevant to measure the IAP during enteral feeding. Feeding intolerance (daily caloric intake less than 500 kcal) can be caused by IAH [36]. On the other hand, studies showed, that there is only a marginal increase in IAP during enteral nutrition, and never in the range of ACS [8].…”
Section: Iah and Enteral Nutritionmentioning
confidence: 99%